Micellar solubilisation of cholesterol is essential for absorption in humans. Issue 2 (11th January 2006) - Woollett, L A; Wang, Y; Buckley, D D; Yao, L; Chin, S; Granholm, N; Jones, P J H; Setchell, K D R; Tso, P; Heubi, J E
Abstract : Background and aims: Intralumenal bile acid (BA) concentrations have a profound effect on cholesterol absorption. We performed studies to assess the effects of markedly reduced lumenal BA on cholesterol absorption in children with inborn errors in BA synthesis and the role of micellar solubilisation of cholesterol on its absorption in an animal model using human intestinal contents. Methods: We studied five subjects: two with 3β hydroxy-C27 steroid dehydrogenase isomerase deficiency (3-HSD), two with Δ 4 -3-oxosteroid 5β reductase deficiency (5β reductase), and one with 2-methylacyl CoA racemase deficiency (racemase). Subjects were studied on supplemental BA therapy and three weeks after withdrawal of supplements. During each treatment period a liquid meal was consumed. Duodenal samples were collected and analysed, and cholesterol absorption and cholesterol fractional synthetic rates were measured. Human intralumenal contents were infused in a bile diverted rat lymph fistula model to assess micellar versus vesicular absorption of cholesterol. Results: Without BA supplementation, intralumenal BA concentrations were below the critical micellar concentration (CMC) whereas intralumenal BAs increased to above the CMC in all subjects on BA supplementation. Lumenal cholesterol was carried primarily as vesicles in untreated subjects whereas it was carried as both micelles and vesicles in treated subjects. Cholesterol absorption increased ≈55% in treated compared with untreated subjects (p = 0.041), with a simultaneous 70% decrease in synthesis rates (p = 0.029). In the rat lymph fistula model, minimal vesicular cholesterol was absorbed whereas vesicular and micellar fatty acid and phospholipid were comparably absorbed. Conclusions: Increasing micellar cholesterol solubilisation by supplemental BA in subjects with inborn errors of BA synthesis leads to an improvement in cholesterol absorption and reduction in cholesterol synthesis due to improved micellar solubilisation of cholesterol.